Multi-field regulated reversible nano-crack film and application thereof
By depositing tellurium film on the PMN-PT ferroelectric single crystal substrate, the reversible opening and closing of nanocrack films and multiple resistance switching is achieved by utilizing the ferroelectric domain flip and light effects induced by light and electric field, the existing technology is solved The memory reading speed and power consumption issues have achieved efficient and low-power memory functions.
Patent Information
- Application Number
- CN202411547785.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-02-18
AI Technical Summary
While the prior art improves the memory reading speed and reduces power consumption, there are problems such as small lattice strain effect control amplitude, high ferroelectric field effect process requirements and large static power consumption, which limits its widespreadness in practical applications. .
Using a multi-field regulation reversible nanocrack film, the tellurium film is deposited on the PMN-PT ferroelectric single crystal substrate, and the combination of light, electric field-induced ferroelectric domain flip and light effect can achieve reversible opening and closing of nanocracks and Multiple resistive state switching.
It realizes multiple switching and efficient regulation of film resistance state, which can improve the memory reading speed while low power consumption. It is suitable for building optoelectronic devices with photodetector and memory functions, and provides new for polymorphic memory devices. Ideas.
Smart Images

Figure CN119486581A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a reversible nanocrack film, in particular to a multi-field regulated reversible nanocrack film and application thereof, belonging to the technical field of functional film / ferroelectric heterojunction. Background Art
[0002] With the development of big data, artificial intelligence, and the Internet of Things, consumer electronics products such as mobile phones and computers are increasingly in need of high-quality, high-computing speed, high-density, and low-power chips to cope with the growing needs of data processing and storage. Therefore, it is urgent to accelerate the development of new memory that can both increase computing speed and reduce energy consumption.
[0003] At present, when computers based on the von Neumann architecture perform calculations, data must be repeatedly transferred between the computing unit (CPU or GPU) and the memory, which limits the overall efficiency and computing time, and causes a large amount of energy consumption, resulting in the so-called "memory wall". In order to overcome the limitations brought by the "memory wall" and improve computing performance, it is very necessary to make the memory more closely integrated with computing resources.
[0004] Therefore, it is particularly important to build a new type of non-volatile memory with low power consumption, high reading speed and integrated visual sensing and signal processing.
[0005] With the development of ferroelectric materials, people have begun to try to apply high-performance ferroelectric materials to fields such as memory. Since ferroelectric devices have the advantages of non-volatility, fast reading speed and low power consumption, they are considered to be a new type of non-volatile memory with great application prospects.
[0006] Compared with devices with a single ferroelectric layer as the core component, devices with functional thin film / ferroelectric heterojunction as the core structure have the advantages of non-destructive reading, high storage density, and multi-functions. By applying an external electric field to the thin film / ferroelectric heterojunction, the electrical, magnetic, and optical properties of the functional device can be controlled by using ferroelectric materials as the gating medium.
[0007] Applying an electric field to a thin film / ferroelectric heterojunction usually produces two control mechanisms: lattice strain effect and interface charge effect. The inverse piezoelectric effect in the ferroelectric layer causes in-plane strain, which is then transmitted to the thin film layer, causing changes in its lattice strain-related physical properties. This control mechanism is called the lattice strain effect. On the other hand, when the polarization direction in the ferroelectric substrate is reversed, the polarization charge on the substrate surface attracts or repels the carriers of the thin film to the interface, thereby changing the carrier concentration in the film and its related electrical properties. This is the interface charge effect, also known as the ferroelectric field effect. However, the control amplitude produced by the lattice strain effect is small, the ferroelectric field effect has high requirements on the preparation process of the thin film, and both effect devices have static power consumption, which is not conducive to practical applications. Summary of the invention
[0008] To address the deficiencies of the prior art, the present invention aims to provide a reversible nanocrack film.
[0009] In order to achieve the above object, the present invention adopts the following technical solution:
[0010] A reversible nanocrack film controlled by multiple fields, characterized in that the nanocrack film is a tellurium film deposited on a PMN-PT (001) ferroelectric single crystal substrate;
[0011] Under the combined effects of light, electric field-induced ferroelectric domain reversal and light effects, the nanocracks on the surface of the tellurium film can be reversibly opened and closed, and multiple resistance state switching can be achieved.
[0012] The electric field strength is E G =Pulsed electric field of ±2kV / cm.
[0013] The thickness of the tellurium thin film is 50-100 nm.
[0014] The wavelength of the above-mentioned light is 405nm-980nm.
[0015] Furthermore, the wavelength of the light is 405 nm and the energy density is 0.942 W / cm 2 .
[0016] Furthermore, the electric field is used to regulate the substrate to be in a positive polarization state; and the light illumination is used to induce switching behavior of the thin film resistor through the generated photogenerated carriers.
[0017] Furthermore, the electric field is used to regulate the substrate to be in a negative polarization state; and the light illumination is used to induce switching behavior of the thin film resistor by providing heat.
[0018] The above-mentioned reversible nanocrack film is used as a nanocrack switch.
[0019] The above-mentioned nanocrack switch is applied in multi-state memory.
[0020] The present invention is beneficial in that:
[0021] A reversible nanocrack film of the present invention uses a pulsed laser deposition method to prepare a high-quality Te / PMN-PT heterojunction, and jointly regulates the resistance state of the Te film by applying a light field and an electric field parallel to the thickness direction of PMN-0.29PT (001), including:
[0022] (1) When the substrate is not polarized, lasers with wavelengths of 405nm, 525nm, and 980nm are selected to perform optical field control on the Te film. The shorter the wavelength, the higher the energy, the more electron-hole pairs generated inside the film, the larger the photocurrent, and the greater the change in film resistance.
[0023] After the light is turned off, the photogenerated electron-hole pairs gradually recombine, the carriers inside the film return to equilibrium, and the film resistance returns to its initial state. The greater the laser energy density, the more electron-hole pairs are generated, and it takes longer to return to the original resistance state.
[0024] (2) Applying a pulsed electric field changes the polarization state, which exhibits different regulatory phenomena when coupled with light.
[0025] When the substrate is in a positive polarization state, the regulation of light on the film resistance is weakened. In the positive polarization state, the defects inside the film increase, which makes it easy to capture photogenerated carriers, thus weakening the regulation of photogenerated carriers on the film resistance.
[0026] When the substrate is in a negative polarization state, the regulation effect of light on the film resistance is significantly enhanced. The increase in substrate temperature caused by laser irradiation causes the ferroelectric domain to disappear or deactivate, thereby healing the nanomechanical cracks on the film surface and reducing the film resistance.
[0027] The reversible nanocrack film of the present invention utilizes an electric field to change the polarization state and photogenerated carriers and heat generated by a light field to jointly regulate the film resistance state. The prepared Te film / ferroelectric heterojunction can be regulated not only by an electric field but also by light. It can be used to construct a photoelectric device having both photodetector and memory functions, and provides a new idea for constructing multi-state memory devices, having strong practicality and wide applicability. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Schematic diagram of spark plasma sintering device.
[0029] Figure 2 This is the XRD diffraction pattern of Te powder.
[0030] Figure 3 (a) AFM image of the surface morphology of Te film; (b) AFM image of Te film with a thickness of 100 nm, and the inset is the SEM image of the cross section of Te / PMN-PT.
[0031] Figure 4 (a) is the IV curve of the film under dark conditions; (b), (c) and (d) are the IV curves of the film under incident light of different powers and wavelengths of 405nm, 525nm and 980nm, respectively.
[0032] Figure 5 Schematic diagram of the internal polarization direction of PMN-0.29PT when the substrate is in positive and negative polarization states (Figures ab).
[0033] Figure 6 (a)-(c) The substrate is in the positive polarization state, the wavelength is 405nm, 525nm, 980nm, and the power density is 0.275W / cm 2 、0.570W / cm 2 , 0.751W / cm 2 and 0.942W / cm 2 The relative change of the resistance of Te film over time under the condition of laser irradiation and continuous switching on and off.
[0034] Figure 7 The curves of the Hall resistance of Te film changing with magnetic field when the substrate is in unpolarized, positively polarized and negatively polarized states.
[0035] Figure 8 (a) The substrate is in a negative polarization state, the wavelength is 405nm, and the power density is 0.942W / cm 2 The relative change of the resistance of Te film with time under laser irradiation; (b) The wavelength is 405nm and the power density is 0.942W / cm 2 (a) The laser irradiation time and temperature change curve; (c) The temperature and resistance change curve.
[0036] Fig. 9 (a) Optical morphology of Te film in negative polarization state; (b)-(d) Optical morphology of the film surface after illumination for 10s, 60s and removal of illumination. DETAILED DESCRIPTION
[0037] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0038] A. Preparation of Te target
[0039] The instrument is a spark plasma sintering system of Sumitomo SPS-2040 produced in Japan.
[0040] like Figure 1 Shown is a schematic diagram of a spark plasma sintering device.
[0041] Weigh 5g Te powder (99.99%) and put it into a 20mm graphite mold, then put it into the SPS cavity. Then heat it to 658K, apply a pressure of 50MPa, sinter for 8min, then cool it down to room temperature, and take out the sintered target. Finally, scrape off the carbon paper covering the surface of the target, and polish the target with metallographic sandpaper until it is smooth before use.
[0042] Scrape the surface of Te target to obtain powder for XRD diffraction characterization, such as Figure 2 As shown, the diffraction peak of the Te target corresponds to the standard Te-PDF#30-1452 diffraction card, indicating that the target is a one-dimensional spiral chain structure.
[0043] The present invention uses a CuKα1 radiation X-ray diffractometer (SmartLab, Rigaku).
[0044] B. Preparation of Te / PMN-PT heterojunction
[0045] According to the parameters shown in Table 1, a Te film with a thickness of 50-100 nm was grown on a (001) oriented and single-sided polished PMN-0.29PT ferroelectric single crystal substrate with a size of 5 mm×5 mm×0.5 mm using pulsed laser deposition technology.
[0046] The PMN-0.29PT single crystal substrate and Te target were placed in the vacuum deposition chamber. When the vacuum degree reached 1×10 -5 After Pa, argon gas at a certain pressure was passed, and a KrF laser (λ=248 nm) was used to ablate the Te target.
[0047] The distance between the target and the substrate is 5 cm, and the laser energy density is set to 1.5 J / cm 2 , the laser frequency is 5Hz.
[0048] After deposition, the sample was annealed in situ for 1 h and then cooled to room temperature at a rate of 4 °C / min.
[0049] Table 1 Experimental parameters of Te thin films prepared by pulsed laser deposition
[0050]
[0051] In order to perform AFM imaging on the surface morphology of the prepared Te film,
[0052] like Figure 3 As shown in (a), the roughness value of the film is 2.3nm.
[0053] like Figure 3 (b) shows AFM step scanning and cross-sectional scanning electron microscopy (SEM) images, indicating that the thickness of the tellurium film is about 100 nm.
[0054] The scanning electron microscope used in the present invention is a field emission scanning electron microscope produced by Zeiss of Germany, model SUPRA S5SAPPHIRE, which is used to measure the surface morphology and thickness of the film.
[0055] C. Control of the resistance state of Te / PMN-PT heterojunction by light
[0056] Lasers with wavelengths of 405 nm, 525 nm, and 980 nm were selected as light stimulation.
[0057] First, test the IV curve of the film under dark conditions. The IV curve is linearly distributed as Figure 4 As shown, it shows that there is an ohmic contact between the film and the gold electrode, which does not affect the transport of electrons in the film and the electrode.
[0058] In order to obtain the resistance response of the film under light, the time of turning the light on and off was controlled, and the change curve of the Te film resistance with the light exposure time was tested.
[0059] 40s of light exposure and 20s of darkness, the effective illumination area of the film is 5×5mm 2 The first 20 seconds are the resistance of the film in the dark, and then the laser is switched on and off.
[0060] Define the resistance of the film when it is illuminated as R(L), and the resistance in the dark as R(D). Then the relative resistance change of the film under light and darkness is ΔR / R=[R(L)-R(D)] / R(D)×100%.
[0061] like Figure 5 As shown in Figures (a)-(c), the wavelengths are 405nm, 525nm, and 980nm, respectively, and the power densities are 0.275W / cm 2 、0.570W / cm 2 , 0.751W / cm 2 and 0.942W / cm 2 The relative change of the resistance of Te film over time under the condition of laser irradiation and continuous switching on and off.
[0062] It can be seen that turning on and off the lasers of three wavelengths and different energy densities will cause the film to produce two stable resistance states. The relative resistance change ΔR / R is negative, and the relative resistance change increases with the increase of optical power.
[0063] This shows that three wavelengths of light can be used as stimulation, with a wavelength of 405nm and a power density of 0.942W / cm 2 The maximum relative resistance change produced by the laser is 50%.
[0064] However, it was observed that at the same wavelength, the greater the laser energy density, the longer it takes for the film to return to its original resistance state. After the light is turned off, the photogenerated electron-hole pairs gradually recombine, the carriers inside the film return to the equilibrium state, and the film resistance increases.
[0065] However, due to the different rates of electron-hole pair recombination, the thin film resistor needs a certain amount of time to return to its original resistance value. The greater the laser energy density, the more electron-hole pairs are generated, and it takes longer to return to the original resistance state.
[0066] D. Regulation of the resistance state of Te / PMN-PT heterojunction by light in the positive polarization state
[0067] By combining light and electric field to regulate the electrical properties of Te / PMN-PT, a polystate memory with high dynamic range can be constructed.
[0068] First, a pulse electric field of +2 kV / cm was applied to the substrate to put it in a positive polarization state, and then the film was irradiated with light for 40 s and then turned off for 20 s.
[0069] Defined in the positive polarization state, the initial resistance of the film is R (Pr + ), the resistance of the film when illuminated is R(Pr + -L), the resistance of the film after turning off the light is R(Pr + -D), so in the positive polarization state, the relative change in film resistance caused by light is ΔR / R = [R(Pr + -L)-R(Pr + -D)] / R(Pr + -D).
[0070] like Figure 6 As shown in Figures (a)-(c), the substrate is in a positive polarization state, the wavelength is 405nm, 525nm, and 980nm, and the power density is 0.275W / cm 2 、0.570W / cm 2 , 0.751W / cm 2 and 0.942W / cm 2 The relative change of the resistance of Te film over time under the condition of laser irradiation and continuous switching on and off.
[0071] In the positive polarization state, light switching can also cause the switching behavior of the thin film resistor. When the substrate is in the positive polarization state, the relative resistance change of the thin film caused by lasers of different wavelengths and different energy densities is smaller than that in the unpolarized state. Among them, the relative change value of the thin film caused by the laser with a wavelength of 405nm and an energy density of 0.942W / cm2 is up to 40%, which is slightly smaller than the relative change of resistance when the substrate is in the unpolarized state (50%).
[0072] Therefore, the positive polarization of the substrate has an inhibitory effect on the regulation of light.
[0073] In order to determine the reason why the positive polarization state inhibits light regulation, the carrier concentration of the film under three polarization states of the substrate was tested under dark conditions, as follows Figure 7 As shown. In the unpolarized state, the slope of the Rxy-B curve is positive, indicating that the carriers of the prepared film are P-type. According to the slope k of the Rxy-B curve and the thickness d of the film, the formula n = 1 / kqd is used to calculate that the carrier concentrations of the film when the substrate is unpolarized, positively polarized, and negatively polarized are 2.29×10 18 cm -3 , 2.20×10 18 cm -3 and 2.35×10 18 cm -3 .
[0074] In the positive polarization state, there are tiny cracks on the surface of the Te film, and defects are formed inside, which leads to the capture of some electron-hole pairs, weakening the regulation effect of the resistance state. Therefore, the relative resistance change of the film regulated by the positive polarization state combined with light is smaller than that of the light regulation alone.
[0075] E. Regulation of the resistance state of Te / PMN-PT heterojunction by light in the negative polarization state
[0076] It can be seen that λ=405nm, P=0.924W / cm 2 Laser has the best control effect on the high and low resistance state switching of Te film.
[0077] Therefore, we choose λ = 405 nm and P = 0.924 W / cm 2 The laser was used to illuminate the film with cracks on the surface in a negatively polarized state in a heat preservation environment. The test results are as follows Figure 8 As shown in (a), the film was in a dark environment for the first 20 seconds, and the resistance was 21M. Under an optical microscope, multiple obvious cracks were observed on the film surface. The laser was turned on for illumination at the 20th second, and it was observed that the film resistance suddenly dropped to a stable 2M after 15 seconds of illumination. The relative resistance change reached 904%, which was much higher than the relative resistance change caused by illumination when the substrate was unpolarized and positively polarized (40-50%).
[0078] Therefore, it is speculated that the resistance change caused by light in the negative polarization state is not caused by photogenerated carriers.
[0079] Considering that the laser energy is high, a large amount of heat will be delivered to the sample when it irradiates it, so the curve of the change of sample temperature with the irradiation time is tested. Figure 8 As shown in (b), after 15 seconds of illumination, the surface temperature of the film quickly rises to 130°C. In order to eliminate the effect of photogenerated carriers, a heating table is used to heat the Te / PMN-PT heterojunction with the substrate in a negative polarization state, and the change curve of the Te film resistance with temperature is tested, as shown in Figure 8(c) When the temperature reaches 130℃, the film resistance suddenly drops to about 2M, which is consistent with the sudden change of the film resistance to 2M after 15s of light exposure. In addition, Figure 8 (a) shows that after 65 seconds of illumination, the film resistance suddenly drops to 1M, and then the resistance remains relatively stable until the light is removed at 80 seconds. Figure 8 (b) It can be seen that after 30 seconds of illumination, the surface temperature reaches about 165°C, and then the temperature maintains a relative equilibrium state, indicating that the film and the surrounding environment have reached a heat exchange equilibrium state. This temperature platform is consistent with Figure 8 (a) corresponds to the resistance platform. Figure 8 (c) When the film is heated to 165°C using a heating table, the film resistance is around 1M, which is similar to Figure 8 The phenomena in (a) and 8(b) are consistent, further indicating that in the negative polarization state, the change in the resistance of the illuminated film is related to the increase in temperature.
[0080] The prior art shows that the conductivity of Te-based thin films increases first and then decreases with increasing temperature. The change range in the range of 25-90°C is about 0.1-25%, which is much smaller than the relative resistance change in this experiment. Therefore, it is speculated that the change behavior of the film resistance with temperature in the present invention is not the intrinsic behavior of the film.
[0081] When a negative polarization electric field is applied to the substrate, a 109° domain flip occurs inside the substrate, causing tensile stress. The stress is transmitted to the Te film through the interface, which eventually causes the opening of nanomechanical cracks in the film and a significant increase in resistance. Therefore, the surface morphology of the film after 15s, 65s and removal of illumination is tested simultaneously, such as Fig. 9 When the film is exposed to light for 15 seconds, the large cracks on the film surface slowly heal, corresponding to the film resistance suddenly changing to 2M; after 65 seconds of light exposure, some small cracks on the film surface further heal, and the film resistance changes to 1M; after the light is removed, there are still cracks on the film surface that have not been completely closed, so the film resistance is still 1M.
[0082] Combined with the optical morphology of the resistance state-temperature curve and the illumination time, it can be seen that the resistance state mutation of the Te film caused by illumination in the negative polarization state is caused by temperature-induced healing of the Te film surface. PMN-PT single crystal Curie temperature T C At 130-170℃, the temperature of the Te / PMN-PT heterojunction surface is as high as 160℃ after 15s of illumination, causing PMN-PT to transform from a ferroelectric phase to a paraelectric phase. The polarization disappears immediately, and the crystal undergoes a phase transition from polarized to non-polarized.
[0083] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the above embodiments do not limit the present invention in any form, and any technical solution obtained by equivalent replacement or equivalent transformation falls within the protection scope of the present invention.
Claims
1. Multi-field controlled reversible nanocrack film, characterized in that: The nanocrack film is a tellurium film deposited on a PMN-PT (001) ferroelectric single crystal substrate; Under the combined effects of light, electric field-induced ferroelectric domain reversal and light effects, the nanocracks on the surface of the tellurium film can be reversibly opened and closed, and multiple resistance state switching can be achieved.
2. The reversible nanocrack film according to claim 1, characterized in that: The electric field is of field strength E G = Pulsed electric field of ±2kV / cm.
3. The reversible nanocrack film according to claim 1, characterized in that: The tellurium thin film has a thickness of 100 nm.
4. The reversible nanocrack film according to claim 1, characterized in that: The wavelength of the light is 405nm-980nm.
5. The reversible nanocrack film according to claim 4, characterized in that: The wavelength of the light is 405nm and the energy density is 0.942W / cm 2 .
6. The reversible nanocrack film according to claim 2, characterized in that: The electric field is used to regulate the substrate to be in a positive polarization state; the light illumination is used to induce switching behavior of the thin film resistor through the generated photogenerated carriers.
7. The reversible nanocrack film according to claim 2, characterized in that: The electric field is used to regulate the substrate to be in a negative polarization state; the light is used to induce switching behavior of the thin film resistor by providing heat.
8. Use of the reversible nanocrack film according to any one of claims 1 to 7 as a nanocrack switch.
9. Use of the nanocrack switch according to claim 8 in a multi-state memory.